2003
DOI: 10.1002/pola.10673
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of ethylene oxide with a calixarene‐based precursor: Synthesis of eight‐arm poly(ethylene oxide) stars by the core‐first methodology

Abstract: Eight-arm poly(ethylene oxide) (PEO) stars were prepared by the core-first method with a newly designed octahydroxylated precursor. This compound was readily obtained in two steps from commercially available tert-butylcalix [8]arene. The choice of the proper solvent of polymerization proved crucial to obtain PEO star materials with a narrow distribution of molar masses. For instance, the use of dimethyl sulfoxide (DMSO) resulted in PEO samples of rather large polydispersities (PDI: 1.3-1.5). In this solvent, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
44
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 33 publications
2
44
0
Order By: Relevance
“…Innovative strategies developed in recent years to overcome the intrinsically low loading capacity of PEG have been dendronization of PEG [45,46] or the synthesis of star-or dendrimer-like PEGs. [39,[47][48][49][50] As in the case of block copolymers based on PEG combined with monomers other than epoxides, for example, N-carboxy anhydrides, either the polymer structure or the chemical composition are significantly different from the established PEG homopolymer. [51][52][53][54][55][56] Considering the desired features, it is surprising that both linear block and random copolymers of ethylene oxide (EO) and appropriate epoxide comonomers represent a rather neglected class of polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Innovative strategies developed in recent years to overcome the intrinsically low loading capacity of PEG have been dendronization of PEG [45,46] or the synthesis of star-or dendrimer-like PEGs. [39,[47][48][49][50] As in the case of block copolymers based on PEG combined with monomers other than epoxides, for example, N-carboxy anhydrides, either the polymer structure or the chemical composition are significantly different from the established PEG homopolymer. [51][52][53][54][55][56] Considering the desired features, it is surprising that both linear block and random copolymers of ethylene oxide (EO) and appropriate epoxide comonomers represent a rather neglected class of polymers.…”
Section: Introductionmentioning
confidence: 99%
“…An extensive amount of work has already been completed on the use of multifunctional initiators in controlled/living polymerizations such as atom transfer radical polymerization (ATRP),5–7 nitroxide‐mediated polymerization (NMP),8 reversible addition–fragmentation chain transfer polymerization (RAFT),9, 10 cationic polymerization,11–13 and anionic polymerization 14, 15. Recent reviews on the use of multifunctional initiators in controlled/living polymerizations include those written by Matyjaszewski (ATRP),16 Hawker et al (NMP),17 Barner et al (RAFT),18 Charleux and Faust (cationic),19 and Hadjichristidis et al (anionic) 20.…”
Section: Introductionmentioning
confidence: 99%
“…Calixarenes, such as p-t-butylcalix [8]arene (BCA), p-methylcalix [6]arene (MCA), and calix [4]resorcinarene (CRA), are cyclic oligomers with many hydroxy groups and can be used as the cores for the synthesis of star-shaped polymers. Furthermore, Sawamoto 27 and Taton 28 reported that the well-defined star shaped polymers with 4, 6, and 8-arms were prepared by the core-first methods using the calixarene derivatives as multifunctional initiators.…”
mentioning
confidence: 99%